DUKUNGAN KELUARGA DAN MOTIVASI IBU DALAM PEMBERIAN ASI EKSKLUSIF PADA BAYI USIA 0-6 BULAN - Sulastri, Sulastri; Istiqomah, Istiqomah; Meldawati, Meldawati; Handayani, Lisda (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: The low achievement of Exclusive Breastfeeding at the Puruk Cahu Seberang Health Center with an achievement of 8.4% and the low understanding of mothers, families and communities about breast milk so that they throw away colostrum because it is considered dirty. Motivation from within breastfeeding mothers encourages them to behave in providing breast milk. Family support can influence the mother's behavior in breastfeeding and providing Exclusive Breastfeeding. Objective: To find out the correlations between family support and maternal motivation in providing exclusive breastfeeding to infants aged 0-6 months. Method: Quantitative research with a correlational study design with a cross-sectional approach. The study population was 128 breastfeeding mothers aged 0-6 months and a sample of 56 respondents in the Puruk Cahu Sebrang Health Center working area in April 2025, taken using the accidental sampling technique. Data were analyzed using the Spearman Rho test. Result: Family support is mostly in the high category, which is 35 people (62.5%), Mother's motivation in providing exclusive breastfeeding is mostly in the medium category, which is 39 people (69.6%). Conclusion: There is a relationship between family support and mother's motivation in providing exclusive breastfeeding to infants aged 0-6 months in the Puruk Cahu Seberang Health Center with a p-value (0.024<0.05), r = 0.301. It is recommended that the health center provide motivation to mothers in providing exclusive breastfeeding to infants